ETIKA ENDORSEMENT (PROMOSI PRODUK BERBAYAR) INFLUENCER (SEORANG PENGARUH BESAR DI MEDIA SOSIAL) MUSLIM: ANALISIS QS. AN-NISA' AYAT 58 MENURUT TAFSIR AL-MISBAH - Latifatu Zuhriya (Journal of Islamic Shariah and Research Applications, 2026)
The advancement of digital technology has positioned Muslim influencers as central figures in modern marketing strategies; however, this phenomenon is often accompanied by ethical violations such as deceptive behavior and a lack of product transparency. This study aims to reconstruct endorsement ethics by analyzing QS. An-Nisa’ verse 58 through the perspective of Tafsir Al-Misbah by M. Quraish Shihab to address moral challenges in the contemporary creative industry. This study employs a qualitative approach with a content analysis method on exegesis texts to explore in-depth interpretations relevant to social media dynamics. The findings reveal that QS. An-Nisa’ verse 58 encapsulates two fundamental principles for endorsement activities: Amanah (Trustworthiness) and ‘Adl (Justice). In M. Quraish Shihab’s interpretation, Amanah is manifested as a moral responsibility to provide honest reviews, disclose paid partnerships transparently, and verify product compliance (halal status). Meanwhile, the principle of ‘Adl requires influencers to deliver objective, balanced information, avoiding manipulation for unilateral gain. The contextual approach in Tafsir Al-Misbah demonstrates that Quranic values are highly relevant as a normative foundation for establishing an ethical digital marketing ecosystem, where Muslim influencers act not merely as marketers but as guardians of public trust with integrity.